2017
DOI: 10.1111/sji.12573
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐FcγRIIB (CD32) Antibodies Differentially Modulate Murine FVIII‐Specific Recall Response in vitro

Abstract: Fc gamma receptors (FcγRs) for IgG regulate adaptive immune responses by modulating activating and inhibitory signalling pathways within immune cells. Data from a haemophilia A mouse model demonstrate that genetic deletion or blockade of the inhibitory FcγR (CD32) suppresses the formation of antibody-secreting cells (ASCs) in vitro. Mechanisms preventing the FVIII-specific recall response, however, remain unclear. Here, the potential role of CD32 inhibition was studied by differentially modulating receptor act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In agreement with this, in FcγRIIB‐deficient mice, mouse IgG2a ICs enhanced primary Ab responses, development of germinal centers and immunological memory . Inhibition of mouse FcγRIIB with an antagonistic mAb (AT128) has also been shown to suppress recall responses to human FVIII ex vivo, presumably by inhibiting binding of FVIII ICs to FcγRIIB expressed by splenic memory B cells and/or effector cells …”
Section: Fcγriib and Immunizationmentioning
confidence: 59%
“…In agreement with this, in FcγRIIB‐deficient mice, mouse IgG2a ICs enhanced primary Ab responses, development of germinal centers and immunological memory . Inhibition of mouse FcγRIIB with an antagonistic mAb (AT128) has also been shown to suppress recall responses to human FVIII ex vivo, presumably by inhibiting binding of FVIII ICs to FcγRIIB expressed by splenic memory B cells and/or effector cells …”
Section: Fcγriib and Immunizationmentioning
confidence: 59%
“…The Fcγ receptor, specifically the inhibitory FcγRIIb (CD32), has been described as the primary mediator of endocytosis of FVIII-IC by DC and recall of FVIII-specific memory B-cell responses ( 19 , 26 , 36 ). In this study, FcγRIIb/FcγRIII blockade significantly reduced the uptake of FVIII-IC by BMDC derived from FVIII -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, antigen reexposure in mice primed with immune complexes efficiently induces plasma cell memory responses ( 25 ). The Fcγ receptor (FcγR) has been implicated as the mediator of enhanced FVIII internalization when complexed with polyclonal anti-FVIII IgG ( 19 , 26 ). DCs in mice express activating FcγRI and FcγRIII and the inhibitory FcγRIIb, which have different binding affinities for IgG isotypes versus IgG-containing immune complexes ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Case reports and retrospective studies of hemophilia A patients undergoing ITI with rFVIIIFc have suggested a quicker time to tolerization when compared to ITI using conventional FVIII concentrates (17,18). Finally, antibodies targeted to FcγRIIB have been shown to modulate the FVIII immune response (19). Based on this evidence we hypothesize that rFVIIIFc may inhibit FVIII-specific B cells more efficiently than FVIII due to its ability to cross-link the BCR of these cells with FcγRIIB.…”
Section: Introductionmentioning
confidence: 92%
“…Whole splenocytes from naïve or FVIII-exposed mice as well as 413 cells were incubated with varying doses of BDD FVIII (0, 0.1, 0.2, and 0.4 µg/test) or APC-conjugated anti-FcγRIIB (APC anti-FcγRIIB: 0, 0.1, 0.2, and 0.4 µg/test) for 30 min at 4 • C in order to block potential binding sites of rFVIIIFc on these cells. Anti-FcγRIIB antibody clone AT130-2 was used because it has previously been shown to have agonistic effects against its target (24) and prevent binding of FVIII immune complexes to FcγRIIB (19). YFP rFVIIIFc was then added at 0.3 µg/test for 30 min at 4 • C. The amount of YFP rFVIIIFc binding was then measured via flow cytometry (SH800S, Sony).…”
Section: Rfviiifc Binding Assaymentioning
confidence: 99%